EDUKASI USIA LANJUT TENTANG MENOPOUSE - Sri Maharani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Menopause is a period of cessation of menstruation that will be experienced by all women and can not be avoided. Some symptoms of menopause will be experienced by women from mild symptoms to things that can interfere with life. As a result of changing lifestyle patterns that are relaxed, lack of movement and exercise and eating patterns that lead to a ready-to-eat dish containing fat, protein and salt but low in fiber, bring consequences to the development of degenerative diseases such as obesity, diabetes mellitus, diabetes, osteoporosis, disease coronary heart disease (CHD), and hypertension. The problems faced by partners today include the lack of knowledge about menopause, so it is considered necessary to provide counseling to provide knowledge to the elderly to overcome complaints experienced by the elderly in the face of menopause. Community service activities are carried out at the Al-Mutjahidin mosque in Jambi City. Timing in January 2018. The target is the elderly. Community service methods survey approach, lecture, discussion, demonstration / simulation. The results obtained are the elderly are able to understand about menopause. It is recommended that health workers, especially at the Puskesmas, give more information about menopause to the elderly by participating in elderly pengajianpara activities to get information about menopause and can undergo menopause well.